2004
DOI: 10.3989/scimar.2004.68s353
|View full text |Cite
|
Sign up to set email alerts
|

Indications of low macrobenthic activity in the deep sediments of the eastern Mediterranean Sea

Abstract: SUMMARY:The fluxes and budget of organic matter from the oligotrophic surface waters of the eastern Mediterranean to the deep waters are poorly known, and little information is available on past and present macrobenthic activity on the sea floor. Evidence of macrobenthic activity can be direct, through recovery of living organisms or their autochthonous skeletal remains, or indirect, through bioturbation and trace fossils. The evidence of biological activity in deep eastern Mediterranean sediments has been eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…These values are comparable to other pelagic eastern Mediterranean sites (Basso et al, 2004), but are small compared to non-Mediterranean oceanic sites (cf. Boudreau, 1994).…”
Section: Dataset and Parameterssupporting
confidence: 65%
See 4 more Smart Citations
“…These values are comparable to other pelagic eastern Mediterranean sites (Basso et al, 2004), but are small compared to non-Mediterranean oceanic sites (cf. Boudreau, 1994).…”
Section: Dataset and Parameterssupporting
confidence: 65%
“…Boudreau, 1994). This is attributed to the scarcity of macrobenthos in the deep Mediterranean; it has been suggested that meiofauna are responsible for the majority of particle mixing that is observed (Basso et al, 2004). This meagre benthic community is likely the result of a low export of organic matter from oligotrophic surface waters.…”
Section: Dataset and Parametersmentioning
confidence: 94%
See 3 more Smart Citations